OFFICIAL DEVELOPMENT ASSISTANCE (ODA) KANADA DALAM UPAYA MENGURANGI KEMISKINAN DAN MEMPERKUAT HAK ASASI MANUSIA DI NEGARA BERKEMBANG DAN AFRIKA TAHUN 2018-2022 - Putri, Alfredha Shinta; Mutmainna, Atifa Zakiah; Wardoyo, Haidhar Fadhil; Febriansyah, Mochammad Rifki (Department of International Relations Universitas Satya Negara Indonesia, 2024)
This article aims to analyze the provision of Official Development Assistance (ODA) from the Canadian government to developing countries and African countries to reduce poverty and strengthen human rights in 2018-2022. Canada is a developed country that provides a lot of humanitarian assistance to developing countries and African countries. This raises the question, “What is the role of Canadian ODA in reducing poverty and strengthening human rights in developing countries and African countries in 2018-2022?” To help answer the question, the authors use the concept of Humanitarian Financing. ODA provided by Canada in Africa is in the form of financial assistance. In conducting research, this article uses a qualitative research method, namely a literature study by collecting various books, journals, articles, and other sources to be able to answer this problem.